Recent advances in electroanalytical drug detection by porphyrin/phthalocyanine macrocycles: developments and future perspectives. Issue 2 (24th November 2020) - Gonçalves, Josué M.; Iglesias, Bernardo A.; Martins, Paulo R.; Angnes, Lúcio
Abstract : Porphyrins and phthalocyanines used to construct sensors for electroanalytical drug detection. Abstract : Porphyrins and phthalocyanines are promising π-conjugated compounds with fantastic photochemical and electrochemical properties which are present in nature in more systems than we are generally aware. The electrochemical properties of these large aromatic molecules are also unique, endowing them with the ability to catalyze a wide range of redox reactions. The macrocycle core of these molecules is extremely favorable for the complexation of several metal ions, resulting in molecules with tunable properties. Porphyrins and phthalocyanines are able to form highly organized films, with high conductivity and great robustness and their use was explored to build a great number of electrochemical and photoelectrochemical sensors for many varied applications, one among them being drug analysis. This review will focus on the potential of the electrodes modified with attractive porphyrins and phthalocyanines for this application. The papers published in the last 3 years were closely evaluated.